اعادة تصميم شارع لوزة الجلاجل - عواد, انس; النيص, مؤيد (جامعة بوليتكنك فلسطين - كلية الهندسة - مساحة, 2019)
يهدف المشروع إلى إعادة تصميم الشارع الداخلي في بلدة تفوح والمؤدي إلى منطقه لوزة و تصميم التقاطعات الموجودة على امتداد الشارع وذلك بإتباع المواصفات والمقاييس الهندسية. تم اختيار هذا المشروع ألنه يخدم بلدة تفوح الواقعة غرب مدينه الخليل ،حيث تكمن أهمية هذا الشارع في توفير الوقت للتنقل والحركة المرورية للشاحنات من وإلى منطقه لوزة. حيث أنه سوف يتم دراسة واقع البنى التحتي للطريق من حيث االسفلت و االنارة. كما سوف يهتم هذا المشروع بتصميم التقاطعات الواصلة بهذا الشارع بحيث يتم زياده فعالية هذه التقاطعات للخدمة وتسهيل حركة المرور ورفع مستوى الفاعلية لها. وستقوم خطة العمل على رفع مساحي للطريق وتحديد الحجم المروري للطريق والقيام بتصميم مسار الطريق وإتمام التصميم اإلنشائي للطريق بما في ذلك البنى التحتية الالزمة للطريق مع إعادة تصميم التقاطعات بحيث تتناسب مع المواصفات والمقاييس الهندسية . The project aims at redesigning the internal street in the town of Tafouh, which leads to the Luza area and designing intersections along the street, following the engineering .specifications and standards This project was chosen because it serves the town of Tafouh, located west of Hebron, where the importance of this road lies in providing time for traffic and traffic for trucks to and from .Luza area As it will study the reality of the infrastructure of the road in terms of asphalt and lighting. The project will also be interested in the design of intersections connected to this street, so that the efficiency of these intersections will be increased to serve and .facilitate traffic and increase the efficiency of the traffic. The plan of action will provide road surveyors, road size, route design and completion of road construction, including road VI infrastructure, with redesigned intersections to suit engineering specifications and standards.
no of pages 82 , مساحة 1/2019
Keywords: الطرق - تأهيل